2015
DOI: 10.1016/j.jascer.2015.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Intensive particle rearrangement in the early stage of spark plasma sintering process

Abstract: a b s t r a c tThe densification behaviors of 3 mol% yttria-stabilized tetragonal zirconia polycrystal (3Y-TZP) ceramics during spark plasma sintering (SPS) were analyzed both using the master sintering curve (MSC) approach and by evaluating the temperature dependent evolution of density and densification rate. It was found that densification curves could hardly be fitted using one apparent activation energy value by MSC conception, by which it indicated that more than one densification mechanisms were involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 30 publications
(38 reference statements)
0
14
0
Order By: Relevance
“…These changes are normally taking place at approximately 1100 °C, but 950 °C can be accepted as the initial temperature of sTab. enstatite formation [28,30], which was indicated by the change in shrinkage rate at ca 1000 -1050 °C in Fig. 4 .…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…These changes are normally taking place at approximately 1100 °C, but 950 °C can be accepted as the initial temperature of sTab. enstatite formation [28,30], which was indicated by the change in shrinkage rate at ca 1000 -1050 °C in Fig. 4 .…”
Section: Resultsmentioning
confidence: 86%
“…Since the steatite is primarily based on talc, its thermally induced behavior should be determined by the dehydration of talc mineral. Namely, talc incorporates adsorption water and hydroxyl groups situated in the space lattice elements [28]. In pure talc, water is normally eliminated in three stages: 115-200 °C; 350-500 °C, and 600-1050 °C [29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in conductive powder, heating of the particles are mainly due to the Joule effect and for the non-conductive powder like Ti, heating occurs through heat transfer from the die and compressive punches [35]. The Joule effect will initiate rapid heating which can effectively suppress particle coursing and thus favors intensive particle rearrangement [36]. However, densification by particle rearrangement takes place rather rapidly because grains rather than atoms act as the migrating units [36], shrinkage rate of the powdered particle is governed by capillary forces developed in the grain boundary [37], and this information may clarify the observed confirmation of significant higher shrinkage rate and sharp peak found in Cu, Cu-2wt% Nb and Cu-5wt% Nb.…”
Section: Shrinkage Rate Of the Sintered Powders Versus Timementioning
confidence: 99%
“…The Joule effect will initiate rapid heating which can effectively suppress particle coursing and thus favors intensive particle rearrangement [36]. However, densification by particle rearrangement takes place rather rapidly because grains rather than atoms act as the migrating units [36], shrinkage rate of the powdered particle is governed by capillary forces developed in the grain boundary [37], and this information may clarify the observed confirmation of significant higher shrinkage rate and sharp peak found in Cu, Cu-2wt% Nb and Cu-5wt% Nb. This outcome showed that the presence of Cu and Nb as conductive path allows a faster particle rearrangement during the spark plasma sintering at 650 °C.…”
Section: Shrinkage Rate Of the Sintered Powders Versus Timementioning
confidence: 99%